2022
DOI: 10.21203/rs.3.rs-2242361/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A situational analysis of human resource and non-communicable diseases management for community health workers in Chengdu, China: A cross-sectional study

Abstract: Background Non-communicable diseases (NCDs) pose a major challenge to health economic cost and residents’ health status. Community health workers (CHWs) are the gatekeeper of primary health care. Objective This study aimed to conduct a situational analysis of the current human resource and requirement of NCDs-related training in Chengdu with regard to address to understand the suggestions for improvement of challenges and barriers. Methods A descriptive online cross-sectional survey was conducted among CHWs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The findings of the study showed that CHWs undertook a wide range of health care activities related to NCDs, but these were somewhat ad hoc and not well defined in policy. Studies elsewhere also highlight the need for clearer and more specific policy and guidelines on the role of CHWs in NCDs [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study showed that CHWs undertook a wide range of health care activities related to NCDs, but these were somewhat ad hoc and not well defined in policy. Studies elsewhere also highlight the need for clearer and more specific policy and guidelines on the role of CHWs in NCDs [18][19][20].…”
Section: Discussionmentioning
confidence: 99%